Livelihood dynamics and hazard perception in a deltaic landscape: a hydrosocial assessment of riverbank erosion in the lower Meghna River, Bangladesh - Popke, Jeff; Rahman, Mizanur (Frontiers in Water, 2025)
Delta regions represent unique settings characterized by a combination of dynamic hydrological environments and livelihood opportunity. They are sites of intensive human activity and infrastructure development aimed at managing the environment and ameliorating hazards such as riverbank erosion. In this paper, we present a case study from the Meghna River delta highlighting livelihood dynamics in the context of riverbank erosion and the recent construction of a protective concrete revetment. To account for the hydrological, socioeconomic, and infrastructural dynamics of the delta environment, we characterize our setting as a hydrosocial territory, and we draw from interviews with local residents to document key dimensions of delta life within the Meghna estuary. Our findings show that the delta environment provides opportunity for local residents, but that riverbank erosion has led to significant displacement and is a source of anxiety for many. We also find that both the nature of the hazard and the limited extent of the new embankment have led to an uneven hydrosocial territory characterized by social and spatial inequality. Despite ongoing challenges, our study shows that riverside dwellers are active agents who manage to craft unique hybrid livelihoods from within the Meghna floodplains.